Role of innate T cells in necrotizing enterocolitis - Liu, Jianyun; Joseph, Sharon; Manohar, Krishna; Lee, Jasmine; Brokaw, John P.; Shelley, W. Christopher; Markel, Troy A. (Frontiers in Immunology, 2024)
Necrotizing enterocolitis (NEC) is a destructive gastrointestinal disease primarily affecting preterm babies. Despite advancements in neonatal care, NEC remains a significant cause of morbidity and mortality in neonatal intensive care units worldwide and the etiology of NEC is still unclear. Risk factors for NEC include prematurity, very low birth weight, feeding with formula, intestinal dysbiosis and bacterial infection. A review of the literature would suggest that supplementation of prebiotics and probiotics prevents NEC by altering the immune responses. Innate T cells, a highly conserved subpopulation of T cells that responds quickly to stimulation, develops differently from conventional T cells in neonates. This review aims to provide a succinct overview of innate T cells in neonates, encompassing their phenotypic characteristics, functional roles, likely involvement in the pathogenesis of NEC, and potential therapeutic implications.